Análises bioinformáticas de proteínas de resistência do tipo nucleotide binding site-leucine rich repeat (NBS-LRR) de café - Ortiz Morazán, Andrés Santiago (2019)
The molecular factors involved in the coffee’s resistance to rust and other diseases have not been completely known, but related projects have been developed since the last century. One of the main problems that make difficult to identify these factors is the lack of a stable version of the Coffea arabica genome. The organization World Coffee Research (WCR) recently made available its version of the C. arabica genome made out of Next Generation Sequencing (NGS) technology. It is known that the pathogenic relations of rust and coffee include effector proteins interacting with the plant’s NBS-LRR proteins, which activate its immune response, normally resulting on a Hypersensitivity Response (HR). The coffee’s resistance gene SH3 codifies a protein similar to the class Coiled Coil-NBS-LRR and the plants that include that gene show a vertical resistance to rust. Looking for factors similar to gene SH3 could lead to new resistance factors able to be used in the development of new coffee varieties with vertical resistance to rust. Through this research it was possible to identify sequences of protein exclusively present in genomes of the Coffea plants, as well as features differentially present in sequences of Arabica and robusta coffee. It was also possible to identify the chromosome localization of the identified sequences. Finally, the results of this research allowed classifying and systematizing all the candidate proteins to use them in coffee genetic improvement programs.